2006
DOI: 10.1007/s10832-006-9639-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a sensor substrate using functionalized mesoporous silica on a gold film for surface plasmon resonance (SPR) spectroscopy

Abstract: The use of surface plasmon resonance (SPR) spectroscopy has been applied to a wide variety of fields such as biosensors and surface analysis instruments. In general, a SPR substrate is prepared using self-assembled monolayer (SAM) method of organic molecules as receptor for the target on a layer of gold or silver. However, mesoporous inorganic materials such as SBA-15 have benefits as sensor substrate for SPR. Mesoporous silica has a large surface area which receptor molecule can be attached and has a rigid bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These materials did not rely on dye incorporation but instead used a metal chelating functional group together with spectrophotometric quantification of Cu 2+ (blue) or Cr 6+ (yellow). Mercaptopropyltriethoxysilane functionalized SBA-15 has been used to enhance surface plasmon resonance signals on a gold substrate [67, 68]. Hybrid thiol-SBA-15 particles were deposited on Au, and the remainder of the Au surface was functionalized with 1,6-hexanedithiol (HDT).…”
Section: Metal Cation Sensorsmentioning
confidence: 99%
“…These materials did not rely on dye incorporation but instead used a metal chelating functional group together with spectrophotometric quantification of Cu 2+ (blue) or Cr 6+ (yellow). Mercaptopropyltriethoxysilane functionalized SBA-15 has been used to enhance surface plasmon resonance signals on a gold substrate [67, 68]. Hybrid thiol-SBA-15 particles were deposited on Au, and the remainder of the Au surface was functionalized with 1,6-hexanedithiol (HDT).…”
Section: Metal Cation Sensorsmentioning
confidence: 99%
“…These porous surfaces can be applied to the SPR substrate by spin coating or electrostatic self-assembly (ESA). Porous surfaces increase the surface area, providing the ability to incorporate receptor sites for biochemical reactions with their corresponding analytes [44]. Porous surfaces have been applied to silica-based films, but often these films are thicker than the SPR evanescence wave and cannot be used for SPR sensory studies.…”
Section: Physical Nanostructuring Of the Filmsmentioning
confidence: 99%
“…As for the sensitivity of the porous surfaces, the work by Oh et al [44] demonstrated an increase in sensitivity compared to nonporous surfaces. Oh and colleagues used an inorganic mesoporous silica (SBA-15) suspension treated with (3mercaptopropyl) trimethoxysilane (MPTMS) to attach thiol groups.…”
Section: Physical Nanostructuring Of the Filmsmentioning
confidence: 99%
See 2 more Smart Citations